Astragalus Polysaccharides/Chitosan Microspheres for Nasal Delivery: Preparation, Optimization, Characterization, and Pharmacodynamics - Wang, Saisai; Sun, Yuqing; Zhang, Jingjing; Cui, Xiaoming; Xu, Zhilu; Ding, Dejun; Zhao, Limin; Li, Wentong; Zhang, Weifen (Frontiers in Pharmacology, 2020)
Chitosan (CTS) constitutes a promising area in treatment of nose-related diseases as a nasal drug delivery carrier. Astragalus polysaccharides (APS) significantly attenuates eosinophils and neutrophil-dominant airway inflammation and it can have potential pharmaceutical application in treatment of severe asthma. The purpose of this work was to prepare APS/CTS microspheres intended for nasal drug delivery by spray drying method. The characteristics of APS/CTS microspheres were evaluated by scanning electron microscope, Fourier transform infrared spectroscopy, differential scanning calorimetry and in vitro drug release. The effect of APS/CTS microspheres on rats with allergic rhinitis was investigated by eosinophils and neutrophils count in nasal lavage fluid. Results of SEM showed that microspheres were spherical and wrinkled. In vitro release showed that 67.48-93.76% APS was released from APS/CTS microspheres at pH 6.8 within 24 h. APS/CTS microspheres had no liver and kidney toxicity by hematoxylin-eosin staining observation, and alleviated allergic symptoms, and reduced eosinophils infiltration and expression of interleukin-4 in nasal mucosa tissue of rats. In conclusion, these results indicated that APS/CTS microspheres had excellent characterizations for treatment of allergic rhinitis.